Synthesis of carbon-based quantum dots from starch extracts: Optical investigations - Al-Douri, Yarub; Badi, Nacer; Voon, Chun Hong (Wiley, 2017)
Carbon-based quantum dots (C-QDs) were synthesized through microwave-assisted carbonization of an aqueous starch suspension mediated by sulphuric and phosphoric acids. The as-prepared C-QDs showed blue, green and yellow luminescence without the addition of any surface-passivating agent. The C-QDs were further analyzed by UV−vis spectroscopy to measure the optical response of the organic compound. The energy gaps revealed narrow sizing of C-QDs in the semiconductor range. The optical refractive index and dielectric constant were investigated. The C-QDs size distribution was characterized. The results suggested an easy route to the large scale production of C-QDs materials.